Status of Joint forest Management Plantations on Removal of Physical Barriers in Utiara Kannada District, Karnataka - Hegde, G. T.; Murthy, I. K.; Ravindranath, N. H.; Bhat, D. M. (Indian Forester, 2011)
Six villages practicing Joint Forest Managementwere selected in Uttara Kannada district, Western Ghats for comparing the status of JFPM plantations over the period of five years (1999-2000 to 2004-05) of physical protection and watchman. Species number, species diversity stem density, basal area and biomass of planted species, recruits and shrub density and diversity were compared between two observations in all the selected villages. All village forests experienced decrease in number of stems and species, while registered increase in shrub species density and diversity. The basal area of trees over a period of five years in absence of protection also has . increased. Statistically significant decrease in stem density of planted species in the plantations of all villages was recorded (42%). The difference in basal area, aboveground biomass and cut stems of planted exotic species and natural species between two observations was statistically significant. The significant change in number of cut stems during the period of community protection indicates diversion of pressure. The significant increase in shrub density and species diversity revealed the partial success of community protection against the grazing and anthropogenic pressure. The study indicates that the JFPM programme should develop strategies that incorporate various measures to conserve and protect the village forests.